An examination of social relations and concussion management via the blue card - Jorgensen, Michael P.; Safai, Parissa; Mainwaring, Lynda (Frontiers in Sports and Active Living, 2024)
Introduction: Initially developed by New Zealand Rugby in 2014, the Blue Card initiative in rugby enables match officials to remove athletes from play if they are suspected to have sustained a concussion. Considerable attention has been paid by sport and health advocates to the possibilities and limitations of this initiative in safeguarding athlete health. However, little if any attention has been paid to the well-being of those responsible for administering the Blue Card (i.e., match officials). The aim of this paper was to examine match officials' experiences with and perspectives on implementing the Blue Card initiative in Ontario, Canada, with focused attention on the tensions around their ability to manage games and participants (e.g., athletes, coaches) while attempting to safeguard athlete well-being. Methods: Using Relational Coordination Theory (RCT) as a guiding framework and qualitative research method, we highlight the rich accounts of 19 match officials' perspectives and experiences regarding sport-related concussion (SRC) management and the Blue Card protocol. Results: Four themes were derived from the data, reflecting latent assumptions embedded within the concussion management process, which include: assumptions of trust, respect, and cooperation; assumptions of shared responsibility; assumptions of shared understanding; and assumptions of harassment-free sport. Discussion: Our findings emphasize the need to attend to social relations in concussion management and provide insight into match officials' fraught experiences on the frontlines of concussion management. We identify factors affecting match official well-being and provide considerations for concussion management initiatives designed to improve athlete safety, such as the Blue Card.